2005
DOI: 10.1074/jbc.m414356200
|View full text |Cite
|
Sign up to set email alerts
|

Lys6-modified Ubiquitin Inhibits Ubiquitin-dependent Protein Degradation

Abstract: Ubiquitin plays essential roles in various cellular processes; therefore, it is of keen interest to study the structure-function relationship of ubiquitin itself. We investigated the modification of Lys 6 of ubiquitin and its physiological consequences. Mass spectrometry-based peptide mapping and N-terminal sequencing demonstrated that, of the 7 Lys residues in ubiquitin, Lys 6 was the most readily labeled with sulfosuccinimidobiotin. Lys 6 -biotinylated ubiquitin was incorporated into high molecular mass ubiq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
79
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 76 publications
(83 citation statements)
references
References 62 publications
4
79
0
Order By: Relevance
“…It appears that an inability to clear Cx43 conjugates that incorporate K6W-Ub results in their accumulation, a backup of this UPS, and, thus, stabilization of the parent protein as well. This mechanism additionally suggests that expression of K6W-Ub may also compromise and saturate the other UPSs, and it provides further rationale as to why cells in which K6W-Ub is expressed have limited capacity to withstand various stresses, particularly proteotoxicity (8,13). Please see SI Text for discussion of relations between monoubiquitination and calpain function and for possible other proteolytic or nonproteolytic mechanisms regulating Cx43, Cx46.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It appears that an inability to clear Cx43 conjugates that incorporate K6W-Ub results in their accumulation, a backup of this UPS, and, thus, stabilization of the parent protein as well. This mechanism additionally suggests that expression of K6W-Ub may also compromise and saturate the other UPSs, and it provides further rationale as to why cells in which K6W-Ub is expressed have limited capacity to withstand various stresses, particularly proteotoxicity (8,13). Please see SI Text for discussion of relations between monoubiquitination and calpain function and for possible other proteolytic or nonproteolytic mechanisms regulating Cx43, Cx46.…”
Section: Discussionmentioning
confidence: 99%
“…Other work showed that Ub mutations in which K6 is replaced by various amino acids, i.e., K6W-Ub, are conjugation competent but proteolytically incompetent. Thus, cells and tissues in which K6W-Ub is expressed accumulate Ub conjugates (13). Exchanging K for A or R has the same effects.…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…Timely removal of abnormal or damaged proteins by the UPP is essential for the cells to withstand and recover from various environmental stresses (Dudek et al, 2005;Shang et al, 2005). However, the UPP itself is also a target of such stresses.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast with many other types of cells, RPE have limited levels of free ubiquitin. Thus, addition of exogenous ubiquitin to RPE supernatant generated significantly higher levels of ubiquitin conjugates and also enhanced the proteasome-dependent proteolysis (Obin et al, 1994(Obin et al, , 1995Shang et al, 2005). The limited levels of endogenous ubiquitin may render the UPP in RPE more vulnerable to a variety of environmental stresses.…”
Section: Introductionmentioning
confidence: 99%